2009
DOI: 10.1002/masy.200950921
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Bone Cements Modified With Bioactive Filler

Abstract: Summary: Bioactive cuttlebone Sepia officinalis particles that contain collagen were used to fill poly (methyl methacrylate-co-styrene) bone cements, varying size and concentration of filler particles. Cuttlebone was characterized by X-ray diffraction and plasma atomic emission spectrophotometer. Maximum reaction temperature and cement setting time were determined for composites and reference (copolymer without filler), along with NMR determination of residual monomer concentration. Mechanical properties chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Theoretically, the modulus of elasticity of bone cement should not be lower than the modulus of the metallic prosthesis and the bone to effectively act as a mechanical buffer. This result is in agreement with the increase in Young's modulus reported in literature 4, 9, 17…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Theoretically, the modulus of elasticity of bone cement should not be lower than the modulus of the metallic prosthesis and the bone to effectively act as a mechanical buffer. This result is in agreement with the increase in Young's modulus reported in literature 4, 9, 17…”
Section: Resultssupporting
confidence: 93%
“…They have been widely used in dentistry and orthopedic surgery for dental cavity filling and fixation of total joint prosthesis of the bone 2, 3. However, conventional bone cements exhibit drawbacks such as poor mechanical properties, inability to bond with bones, high exothermic polymerization temperatures, release of residual monomer, and high shrinkage 4, 5. Therefore, a large number of studies are being carried out on the development of bone cement formulation to improve the mechanical, thermal, handling, and biocompatibility properties of bone cements.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high organic component, the cuttlebone is considered an inorganic−organic structure: 10% of cuttlebone weight is b−chitin linked with proteins (Florek et al 2009), twice the amount found in other mollusc shells (Marin et al 2010). About 90% of shell material is ar− agonite, with small amounts of calcite (Xiao et al 2005) and hydroxyapatite (Jasso−Gastinel et al 2009). The septa are richer in chitin, whereas pillars are richer in aragonite (Florek et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Besides being used as a scaffold, natural CB can also be milled and used to fill poly (methyl methacrylate-co-styrene) bone cements [191,192]. When compared with the non-filled cement, the addition of 10 and 30 wt% of CB resulted in an increase of tensile strength and Young's modulus.…”
Section: Cuttlefish Bonementioning
confidence: 99%
“…Furthermore, the setting time increases with the CB content, which is beneficial to allow enough manipulation time before setting. However, a longer setting time can cause some medical problems because pressure in the prosthesis has to be maintained until the cement sets [192]. When implanted in bone defects, the cements without CB were weakly adherent to the parietal bone while the samples containing CB were strongly attached to the bone, an indication that osteointegration has occurred in samples containing CB [191].…”
Section: Cuttlefish Bonementioning
confidence: 99%